2021
DOI: 10.12669/pjms.37.4.3892
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for pelvic organ prolapse and stress urinary incontinence and female sexual functions: A quasi-experimental study

Abstract: Objectives: To assess the effect of pelvic organ prolapse (POP) and/or stress urinary incontinence (SUI) on various domains of female sexual functions in patients before and after reconstructive surgery for these pelvic floor disorders. Methods: We conducted a quasi-experimental study of 126 women aged 25-65 years, presenting with POP / SUI, from January 1st 2019 to December 31st 2019 at Aga Khan University Hospital. POP surgery was performed only in patients with symptomatic POP ≥ stage 2 according to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(35 reference statements)
0
1
0
Order By: Relevance
“… 18 A previous study showed significant effects of resconstructive surgery on sexual function in women with POP and/or stress incontinence. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 A previous study showed significant effects of resconstructive surgery on sexual function in women with POP and/or stress incontinence. 3 …”
Section: Discussionmentioning
confidence: 99%
“…18 A previous study showed significant effects of resconstructive surgery on sexual function in women with POP and/or stress incontinence. 3 In our study, we included only elderly women and hence sexual function was not a major concern for this population. The morbidity and mortality associated with the surgery is largely related to the health status of this elderly segment of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reluctance to disclose symptoms may underestimate UI prevalence, impacting data accuracy and completeness (Karmarkar et al, 2022;Larsudd-Kåverud et al, 2023). Addressing these limitations is pivotal for a more accurate understanding of UI prevalence (Abrar et al, 2023). Interestingly, over a quarter of women reported experiencing UI for more than five years, but only a fraction sought medical consultation (15.7%).…”
Section: Discussionmentioning
confidence: 99%